Cover Image. Issue 1 (25th January 2021) - Unknown
Abstract : This special issue of Peptide Science presents state‐of‐the‐art peptide research from UK‐based laboratories. Four Reviews on new transformative peptide technologies, including applications of cyclic peptides, bioportides and stapled peptides, begin the issue. Seven original research articles focusing on the development of antimicrobials, a bacterial three‐hybrid screening platform and stapled peptides follow on. These works provide a glimpse of the excellent peptide science occurring in the UK.